An atypical Arp2/3 complex is required for Plasmodium DNA segregation and malaria transmission - Hentzschel, Franziska; Jewanski, David; Sokolowski-Adams, Yvonne; Agarwal, Pratika; Kraeft, Anna; Hildenbrand, Kolja; Dorner, Lilian; Singer, Mirko; Marti, Matthias; Frischknecht, Friedrich (Nature microbiology, 2025)
Plasmodium parasites, the causative agents of malaria, undergo crucial developments within the mosquito vector, initiated by the formation of male and female gametes. Male gametogenesis involves three rapid rounds of mitosis without nuclear or cell division, followed by a single round of DNA segregation and nuclear division during gamete budding. How the cell organizes the segregation of eight genomes from a single octoploid nucleus into eight haploid gametes is currently unknown. Here we discovered an atypical Arp2/3 complex in Plasmodium important for DNA segregation during male gametogenesis. Unlike the canonical Arp2/3 complex found in other eukaryotes, Plasmodium Arp2/3 localizes to endomitotic spindles and interacts with a kinetochore-associated protein. Disruption of Arp2/3 subunits or actin polymerization interferes with kinetochore-spindle association, causes the formation of subhaploid gametes, and blocks transmission. Our work identified an evolutionary divergent Arp2/3 complex in malaria parasites, provides insights into gametogenesis, and reveals potential targets for transmission-blocking interventions.